Virome of Camellia japonica: Discovery of and Molecular Characterization of New Viruses of Different Taxa in Camellias - Zhang, Song; Yang, Liu; Ma, Lisha; Tian, Xin; Li, Ruhui; Zhou, Changyong; Cao, Mengji (Frontiers in Microbiology, 2020)
Many species of the genus Camellia are native to China, and several species such as C. japonica have been cultivated as garden plants for over thousand years. Virus-like symptoms have been recorded for years. In this study, C. japonica plants with various leaf symptoms were observed in the Jiangxi and Chongqing provinces. The species composition of potential viruses in the symptomatic plants was analyzed by next-generation sequencing of six libraries prepared from total RNAs of specimens from 10 trees. Five new viruses were discovered and sequenced and were tentatively named Camellia chlorotic ringspot viruses (CaCRSVs), Camellia yellow ringspot virus (CaYRSV), Camellia-associated badnavirus (CaBaV), and Camellia-associated marafivirus (CaMaV) based on comprehensive analyses. Among these viruses, CaYRSV, CaBaV, and CaMaV share similar genome organizations and clear sequence homology with known viruses in databases and could potentially be classified as new species of the genera Badnavirus, Idaeovirus, and Marafivirus, respectively. In addition, CaCRSVs comprise two distinct viruses, and each likely contains five genomic RNA segments that were found to be distantly related to viral RNAs of members in the genus Emaravirus (family Fimoviridae). The 10 RNAs of CaCRSVs show conserved terminal sequences that differ markedly from those of emaraviral RNAs. These data, together with the phylogenetic analysis, suggest that the evolutionary status of CaCRSVs may represent a novel genus in the family Fimoviridae. In addition, two known viruses (geminivirus and blunervirus) and a mass of betaflexiviruses existing as heterogeneous mixtures were detected, and their roles in symptom formation were studied. Collectively, the information about viral species and the detection protocols that were developed can serve as a basis for the timely prevention and control of these viruses. Distinguishing the virus-related symptoms from genetic characteristics of C. japonica is also significant for breeding efforts.